Qualitative meta-analysis of researches related to hydropolitical relations between Iran and Iraq - zakeyeh aftabi; morad kaveyani Rad (تحقیقات کاربردی علوم جغرافیایی)
Water is a strategic and scarce resource that has become increasingly limited in recent years due to a variety of national and transnational factors, significantly impacting security, stability, development, and prosperity in various countries. The profound influence of water on these domains has positioned it at the forefront of the foreign policy and hydropolitical relations of numerous nations, including those in South West Asia. In recent years, despite the prominence of the water crisis and its implications for the relations between Iran and Iraq within scholarly, political, and media discussions, the complexities of this issue remain poorly understood, leading to disparate interpretations. The current research, which is exploratory in nature, utilized library methods for data collection with the aim of achieving a qualitative understanding of the multifaceted hydropolitical relations between Iran and Iraq. This study not only seeks to identify the content and methodological characteristics of existing literature but also aims to uncover research gaps in this field employing a qualitative meta-analysis approach. Through this method, the research examined 34 studies published between 2014 and 2023, including domestic scientific articles, theses, and contributions to reputable international journals. The findings indicate that a comprehensive analysis of the various dimensions of hydropolitical relations between Iran and Iraq has yet to be undertaken. In this context, the absence of accurate and reliable data, alongside the inadequacy of theoretical and cognitive frameworks, represents significant deficiencies in the existing research on the bilateral relations of these two countries.